Ponderación Constitucional del Derecho a la salud y aplicación frente a los Derechos Fundamentales en pandemia COVID 19 - Andino Cárdenas, Valeria Teresa (2024)
The right to health in Ecuador is recognized as a fundamental right, guaranteed by the Constitution and strengthened by the national legal framework, thus one of the main responsibilities of the State is the effective implementation of the regulations that protect the right to health. . However, during the pandemic caused by the COVID-19 virus, governments were able to take restrictive measures to protect public health. In this sense, the doctrine on the Constitution and health focuses on determining to what extent governments can limit fundamental rights in the name of protecting public health. The present research work examines the constitutional weighting of the Right to health and application compared to Fundamental Rights in the COVID 19 pandemic, for this the exercise of constitutional weighting is doctrinally supported, the situation is determined and finally legal criteria on the weighting are established. constitutional right to health. To carry out what was stated in previous lines, this work is developed under the qualitative approach methodology, making use of the compilation of bibliographic information regarding topics such as the right to health, the weighting of the right to health, Fundamental Rights. Likewise, an analysis is made of the decisions of the Constitutional Court of Ecuador with reference to the State of Exception number 1-20-EE/20; On the other hand, sentence 127-21-IN/23 of Case No. 127-21-IN and accumulated is analyzed, which allows us to show the different situations of constitutional weighting of the Right to health versus fundamental rights during the pandemic. caused by the COVID19 virus within the Ecuadorian jurisdiction.